Prevalence and correlates of QTc prolongation in Italian psychiatric care: cross-sectional multicentre study - Nosè, M. (Epidemiol Psychiatr Sci, 2015)
AIMS. In recent years several warnings have been issued by regulatory authorities on the risk of electrocardiogram abnormalities in individuals exposed to psychotropic drugs. As a consequence of these warnings, monitoring of the QT interval corrected for heart rate (QTc) has become increasingly common. This study was conducted to measure the frequency of QTc prolongation in unselected psychiatric patients, and to document the associated factors using a cross-sectional approach. METHOD. The study was carried out in 35 Italian psychiatric services that are part of the STAR (Servizi Territoriali Associati per la Ricerca) Network, a research group established to produce scientific knowledge by collecting data under ordinary circumstances. During a three-month period, a consecutive unselected series of both in- and out-patients were enrolled if they performed an ECG during the recruitment period and were receiving psychotropic drugs on the day ECG was recorded. RESULTS. During the recruitment period a total of 2411 patients were included in the study. The prevalence of QTc prolongation ranged from 14.7% (men) and 18.6% (women) for the cut-off of 450 ms, to 1.26% (men) and 1.01% (women) for the cut-off of 500 ms. In the multivariate model conducted in the whole sample of patients exposed to psychotropic drugs, female sex, age, heart rate, alcohol and/or substance abuse, cardiovascular diseases and cardiovascular drug treatment, and drug overdose were significantly associated with QTc prolongation. In patients exposed to antipsychotic drugs, polypharmacy was positively associated with QTc prolongation, whereas use of aripiprazole decreased the risk. In patients exposed to antidepressant drugs, use of citalopram, citalopram dose and use of haloperidol in addition to antidepressant drugs, were all positively associated with QTc prolongation. CONCLUSIONS. The confirmation of a link between antipsychotic polypharmacy and QTc prolongation supports the current guidelines that recommend avoiding the concurrent use of two or more antipsychotic drugs, and the confirmation of a link between citalopram and QTc prolongation supports the need for routine QTc monitoring. The relatively low proportion of patients with QTc prolongation not only suggests compliance with current safety warnings issued by regulatory authorities, but also casts some doubts on the clinical relevance of QTc prolongation related to some psychotropic drugs.